Optimization of InAs/GaSb core-shell nanowire structure for improved TFET performance. (October 2019) - Singh, Sankalp Kumar; Kakkerla, Ramesh Kumar; Joseph, H. Bijo; Gupta, Ankur; Anandan, Deepak; Nagarajan, Venkatesan; Yu, Hung Wei; Thiruvadigal, D. John; Chang, Edward Yi
Abstract: The performance of InAs/GaSb core-shell nanowire TFET is systematically investigated for the effects of intrinsic device parameters such as channel doping, shell thickness, spacer length and source offset. Device ON-current (ION ) was chosen as the key figure of merit. It is found that ION improves due to improved electrostatic control achieved by the TFET with optimum shell diameter. The maximum ION obtained for a shell thickness of 2 nm was 33.65 μA/μm and a Subthreshold Swing (SS) of 12.9 mV/decade with an ION /IOFF ratio of 1.49 × 10 8 for our device. Device ION can be further improved by adding an optimum spacer at the source-channel junction. It was also found that device ON-current is almost constant and does not get much affected by having a larger shell offset.